The Application of Electrocoagulation to Treat Meatball Wastewater with Aluminium Electrode - Soeprijanto; Findi Kusuma Wardani; M. Yosi Kurniawan (IPTEK The Journal of Engineering, 2021)
The meatball factory in the Keputih, Surabaya produce meatball liquid waste with a COD value of 11,072 mg/L so it requires special treatment before being discharged into the environment. This research was conducted to treat that meatball liquid waste by electrocoagulation method using aluminum electrodes. The variables were arranged using completely randomized design at pH variations of 5.5 and 9, residence time of 15, 30, 45 and 60 minutes, number of plates of 4 and 8, and current density of 312.5; 375; 156.25; 187.5 A/m2 in batches then will be analyzed for COD, TDS and Turbidity. This research has obtained results that optimal time for electrocoagulation varies from 15-45 minutes then current density of 187.5 and 375 A/m2 are slightly better than 156,25 and 312,5 A/m2 then pH 8 had better treatment results than pH 5.5 especially in turbidity then the use of 8 aluminum plates at the same electric current had far more better results than 4 plates. So that the best efficiency in this wastewater treatment is obtained by removal of COD value up to 94.78%, Turbidity up to 98.68% and TDS up to 76.63% at a current density of 187.5 A/m2 and pH 8 for 30 minutes.